INTUITIONISTIC FUZZY CONTRA ð›„* GENERALIZED OPEN MAPPINGS - M, RIYA V.; D, JAYANTHI (International Journal of Mathematical Archive, 2018)
In this paper, we have introduced the notion of intuitionistic fuzzy ...